Neodymium isotope evidence for glacial-interglacial variability of deepwater transit time in the Pacific Ocean - Rong Hu; Alexander M. Piotrowski (Nature Communications, 2018)
The response of deep Pacific overturning to glacial-interglacial climate change is still debated. Here the authors show a generally faster deep Pacific overturning operated in recent glacial periods based on a novel application of Nd isotopes recorded in foraminifera.